Classroom Management Problems Derives from Gifted and Talented Students’ Leadership Qualities - Çağlar Çetinkaya; Halime Güngör; İlknur Maya Çalışkan (Sakarya Üniversitesi Eğitim Fakültesi Dergisi)
The purpose of this study is to investigate how leadership features of gifted students at primary schools cause classroom management problems. The model of the study is descriptive survey model. In this study, both qualitative and quantitative methods were applied. Raven Standard Progressive Matrices Plus Test (RSPM) was applied to one hundred twenty three primary school students who were chosen randomly from Sakarya City, and seventeen gifted students were identified. Quantitative data was collected by asking closed ended questions to chosen students in order to figure out their leadership features. Qualitative data was collected from the teachers of the students with semi-structured interview form to discover how the identified leadershipfeatures cause problems in classes. It was seen at the end of the study that the class problems stemed from the gifted students' perfectionism, their will to produce their own decisions and solutions, and their not paying attention to the rules of respect and effecting their current group.